Investigating the mutual interactions of 19th century western women and their environment in George Gissing’s New Grub Street and The Nether World - Shabrang, Hoda; Afsharzadeh, Mohammad Hossein (Penerbit Universiti Kebangsaan Malaysia, 2023)
The present article explores an Ecofeministic approach to two novels of George Gissing, New Grub Street (1891), The Nether World (1889) based on the two notions of oppression and domination. George Gissing is the great English writer of the 19th and early 20th centuries, whose real novels can be considered as a reflection of the society of those days. During the 19th century and early 20th century, the urbanization was culminated, and the man’s connection to nature was almost destroyed. This was accompanied by the oppression of women in the patriarchal society of that time which clearly indicates the fact that nature and women are empirically connected. By examining two notions of oppression and domination in Gissing’s novels in this research, the researcher aimed to study the connection of nature and women as they are threatened by the same enemy – a toxic mindset of domination and control that degrades both women and environment to show that women and nature are both oppressed and dominated by masculine rules of patriarchal society of 19th century. The strategies and solutions of the female characters to save themselves and their nature from oppressions and dominations are also studied. This study concluded that the interactions between human and the environment, as well as the oppressive relationship between men and women in 19th century, have been well illustrated and criticized in Gissing novels.